Suspect Freedoms : The Racial and Sexual Politics of Cubanidad in New York, 1823-1957 - Mirabal, Nancy Raquel, 1966- (Book collections on Project MUSE., 2016)
"Beginning in the early nineteenth century, Cubans migrated to New York City to organize and protest against Spanish colonial rule. While revolutionary wars raged in Cuba, expatriates envisioned, dissected, and redefined meanings of independence and nationhood. An underlying element was the concept of Cubanidad, a shared sense of what it meant to be Cuban. Deeply influenced by discussions of slavery, freedom, masculinity, and United States imperialism, the question of what and who constituted 'being Cuban' remained in flux and often, suspect. The first book to explore Cuban racial and sexual politics in New York during the nineteenth and twentieth centuries, Suspect Freedoms chronicles the largely unexamined and often forgotten history of more than a hundred years of Cuban exile, migration, diaspora, and community formation. Nancy Raquel Mirabal delves into the rich cache of primary sources, archival documents, literary texts, club records, newspapers, photographs, and oral histories to write what Michel Rolph Trouillot has termed an 'unthinkable history.' Situating this pivotal era within larger theoretical discussions of potential, future, visibility, and belonging, Mirabal shows how these transformations complicated meanings of territoriality, gender, race, power, and labor. She argues that slavery, nation, and the fear that Cuba would become 'another Haiti' were critical in the making of early diasporic Cubanidades, and documents how, by the late nineteenth and early twentieth centuries, Afro-Cubans were authors of their own experiences; organizing movements, publishing texts, and establishing important political, revolutionary, and social clubs. Meticulously documented and deftly crafted, Suspect Freedoms unravels a nuanced and vital history"--Publisher's website